Method of Determination of Natural Frequencies and Forms of Nonlinear Vibrations for Layered Cylindrical Panels - Marchuk, M. V.; Goriachko, T. V.; Pakosh, V. S.; Lesyk, O. F. (NTU "KhPI", 2016)
The technique of finding a finite number of first natural frequencies for geometrically nonlinear vibrations of layered elongated cylindrical panels at discrete consideration of components is proposed and verified. The influence of the radius of curvature on the natural frequencies of three- and five-layered panels is investigated. The dependence between the volume of filler three-layer panels and the lowest natural frequency has been established.
Keywords: nonlinear vibrations; elongated layered panel; perturbations method; natural frequencies